Forecasting prevalence of dengue hemorrhagic fever using ARIMA model in Sulawesi Tenggara Province, Indonesia - Mistawati Mistawati; Yasnani Yasnani; Hariati Lestari (Public Health of Indonesia)
Background: Dengue hemorrhagic fever occurs through the bite of Aedes mosquitoes, primarily Aedes aegypti, carrying dengue viruses. In recent decades, the risk increased dramatically, not only in the tropics but also in subtropical regions.